2010
DOI: 10.1002/adem.200980067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nonwoven Nanofibers by Electrospinning – A Promising Biomaterial for Tissue Engineering and Drug Delivery

Abstract: PHB nanofibers are synthesized by electrospinning of a PHB solution prepared using HFIP as the solvent. The nanofibrous scaffold supports rapid cell growth with normal morphology and attains a viability of 87% after 48 h. Kanamycin sulphate‐loaded PHB nanofiber mats are synthesized, with the antibiotic on the surface and sandwiched within the nanofiber mats: their antimicrobial property is proved by the good zone of inhibition tested against Staphylococcus aureus. The drug shows more than 95% release within 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The polymer solutions were set at a flow rate of 0.5 mL h −1 with the voltage set at 25 kV and at 17‐cm distance from needle tip and the collector. The nanofibers were deposited onto an aluminum substrate wound around a rotary drum placed perpendicular to the needle …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer solutions were set at a flow rate of 0.5 mL h −1 with the voltage set at 25 kV and at 17‐cm distance from needle tip and the collector. The nanofibers were deposited onto an aluminum substrate wound around a rotary drum placed perpendicular to the needle …”
Section: Methodsmentioning
confidence: 99%
“…The nanofibers were deposited onto an aluminum substrate wound around a rotary drum placed perpendicular to the needle. 21 Surface morphology studies The electrospun fibers were sputter coated with gold and observed under a scanning electron microscope (FEI Quanta FEG 200-HRSEM) operating at an accelerating voltage of 5-20 kV. TEM (TF 20:Tecnai G2) analysis with an accelerating voltage of 5-20 kV and 200 kV, respectively Diameter of about 50 different fibers were measured using the UTHSCSA image tool to obtain their average diameter.…”
Section: Electrospinning Of Polymer Fibersmentioning
confidence: 99%
“…P(R)-HB [93][94][95][96][97], and bacterial copolymers such as P(3HB-co-4HB) [98][99][100], PHBV [101][102][103] or PHBH and derivatives [104][105][106], have been used for the elaboration of self-assembled systems such as DDSs, tissue engineering scaffolds and implants [107][108][109][110]. Those polymers have been chosen for their biodegradability and biocompatibility.…”
Section: Chemically Modified Bacterial Phb-based (Co)polymersmentioning
confidence: 99%
“…Electrospinning, an easy and versatile technique, allows bioactive molecules to be combined with a wide range of additional components and provides a high degree of control over the composition and structure of the produced fibers [6]. Electrospun fibers were widely used in drug delivery [7,8] and wound dressing materials [9,10], attributing to their large surface-to-volume ratio, excellent biocompatibility and biodegradability [11][12][13]. Notably, there has been growing attention to fabricate electrospun fibrous membranes as novel active packaging materials at present [14,15].…”
Section: Introductionmentioning
confidence: 99%